Peran Sekolah dalam Membangun Karakter Toleransi pada Siswa Multikultural - Pohan, Nur Jannah; Dwi JIhan Fahira; Gusmaneli (Jurnal Ilmiah Literasi Indonesia, 2025)
The integration of Islamic values ​​into Islamic Religious Education (PAI) learning design involves more than just presenting theological content, but also designing a learning process that shapes students' faith (iman), practice (amal), and morals (akhlaq). This article outlines the theoretical foundation, design principles, implementation model (adapted from ADDIE), recommended learning methods, value assessment design, case studies, implementation challenges and solution strategies, as well as policy recommendations and teacher professional development. The description is supported by a literature review and recent research on the internalization of Islamic values ​​and the use of technology for character education. .